Mammalian Lass6 and its related family members regulate synthesis of specific ceramides - Mizutani, Yukiko (Portland Press Ltd., 2005)
The Lass (longevity-assurance homologue) family members, which are highly conserved among eukaryotes, function in ceramide synthesis. In the mouse, there are at least five Lass family members, Lass1, Lass2, Lass4, Lass5 and the hitherto uncharacterized Lass6. To investigate specific roles for each Lass member in ceramide synthesis, we cloned these five mouse proteins. Overproduction of any Lass protein in cultured cells resulted in an increase in cellular ceramide, but the ceramide species produced varied. Overproduction of Lass1 increased C(18:0)-ceramide levels preferentially, and overproduction of Lass2 and Lass4 increased levels of longer ceramides such as C(22:0)- and C(24:0)-ceramides. Lass5 and Lass6 produced shorter ceramide species (C(14:0)- and C(16:0)-ceramides); however, their substrate preferences towards saturated/unsaturated fatty acyl-CoA differed. In addition to differences in substrate preferences, we also demonstrated by Northern blotting that Lass family members are differentially expressed among tissues. Additionally, we found that Lass proteins differ with regard to glycosylation. Of the five members, only Lass2, Lass5 and Lass6 were N-glycosylated, each at their N-terminal Asn residue. The occurrence of N-glycosylation of some Lass proteins provides topological insight, indicating that the N-termini of Lass family members probably face the luminal side of the endoplasmic reticulum membrane. Furthermore, based on a proteinase K digestion assay, we demonstrated that the C-terminus of Lass6 faces the cytosolic side of the membrane. From these data we propose topology for the conserved Lag1 motif in Lass family members, namely that the N-terminal region faces the luminal side and the C-terminal region the cytosolic side of the endoplasmic reticulum membrane.